2020
DOI: 10.2147/ott.s243914
|View full text |Cite
|
Sign up to set email alerts
|

<p>Low-Dose Radiation Promotes Invasion and Migration of A549 Cells by Activating the CXCL1/NF-κB Signaling Pathway</p>

Abstract: Radiation has well-known and well-characterized direct toxic effects on cells and tissues. However, low-dose ionizing irradiation (LDIR) can also enhance the invasion and migration of tumor cells, and the mechanisms underlying these effects remain unclear. The present study aimed to investigate changes induced in the migration and invasion of A549 cells after LDIR and to explore the potential molecular mechanism. Materials and Methods: A549 cells were irradiated with X-rays at different doses (0, 2, 4, and 6 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…15,39 Despite great advances in radiotherapy techniques and modalities, recurrence and resistance still limit the therapeutic success. There is evidence that when tumor cells are exposed to low doses of X-rays, their viability and proliferation ability is significantly suppressed, while migration and invasion capabilities are significantly enhanced; [20][21][22] thus, seeking novel approaches or agents to reverse IR-induced tumor cell invasion and migration is the key to overcoming tumor recurrence and metastasis during radiotherapy for NSCLC. Diallyl disulfide, a major organosulfur compound derived from garlic, were reported to exhibit various pharmacological properties such as antibacteria, antiangiogenesis, anticancer, and anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,39 Despite great advances in radiotherapy techniques and modalities, recurrence and resistance still limit the therapeutic success. There is evidence that when tumor cells are exposed to low doses of X-rays, their viability and proliferation ability is significantly suppressed, while migration and invasion capabilities are significantly enhanced; [20][21][22] thus, seeking novel approaches or agents to reverse IR-induced tumor cell invasion and migration is the key to overcoming tumor recurrence and metastasis during radiotherapy for NSCLC. Diallyl disulfide, a major organosulfur compound derived from garlic, were reported to exhibit various pharmacological properties such as antibacteria, antiangiogenesis, anticancer, and anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…9 Besides, DADS are also reported to induce cytotoxicity and induction of cell death in various human cancer cells. 7,21,40 It has been indicated that DADS could suppress cell migration and the invasion in human triple negative breast cancer, 7 colorectal cancer, 20 colon cancer 9,41 and prostate cancer cells. 11 Recently, studies showed that DADS inhibited human colon cancer cell growth, invasion and migration, and reversed the EMT in gastric cancer cells 42 and A549 lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A549 cells were seeded in 6-well plates at a density of 2 × 10 5 cells/well and cultured 24 h to reach 90% con uence as a monolayer. Then the monolayer was scratched with a sterile pipette tip (200 µL type) and washed with PBS twice [41,42]. The cells were treated by the complexes and continued to culture in DMEM containing 10 % FBS for 72 h and the wound areas were measured by microplate reader (Model 550, Bio-Rad, U.S.A) at 12, 24, 36, 48, 60 and 72 h, respectively.…”
Section: Wound Healing Assaymentioning
confidence: 99%
“…After trypsinization, A549 cells were plated in the upper chamber inserted in 24-well plates with serum-free DMEM at a density of 2.0 × 10 4 cells/well, and DMEM with 10 % FBS was added into the lower chamber. After incubation for 24 h, cells in the upper chamber were wiped by cotton swab, and cells migrated to the lower surface were xed with ethanol at 4℃ for 15 min and stained with 0.2 % crystal violet for 30 min [41,42]. The stained cells were then rinsed with PBS and recorded by Olympus uorescence microscope.…”
Section: Transwell Migration Assaymentioning
confidence: 99%